Early Career Academics in Educational Research : Perspectives from Sub-Saharan African Higher Education Sectors - Felix, Alan,; Fru, Raymond Nkwenti,; Mapuyah, Medson,; Ndofirepi, Amasa,; Pietersen, Doniwen,; Sepeng, Percy, (African Higher Education: Developments and Perspectives ;, 2025)
Neoliberal theory on higher education highlights the challenges faced by academics in the "new times" of academia. Quality-improvement programs and academic accountability mechanisms have been advocated, but the profession's precariousness and stress make early career researchers especially vulnerable. The highly competitive funding environment and increased non-research duties put academics' time and dedication at risk. Early career academics can enhance Sub-Saharan African educational research by contributing effectively to contextually relevant research, collaborating with regional colleagues, and pursuing international collaboration and financing. However, more research is needed to understand the experiences of the new generation of academics and their responses to new performativity criteria. Contributors are: Ikechi Agbugba, Wiets Botes, Darrell de Klerk, Alan Felix, Claire Gaillard, Dean Langeveldt, Bheki Mngomezulu, Thembeka Myende, Amasa Ndofirepi, Ntombikayise Nkosi, Felix Okoye, June Palmer, Doniwen Pietersen, Percy Sepeng, Kevin Teise, Victor Teise and Yusef Waghid.